Quality of care in the last year of life: adaptation and validation of the German "Views of Informal Carers' Evaluation of Services - Last Year of Life - Cologne" - Gloria Dust; Nicolas Schippel; Stephanie Stock; Julia Strupp; Raymond Voltz; Christian Rietz; On behalf of the CoRe- (BMC, 2022)
Abstract Background To inform quality improvement and strengthen services provided in the last year of life, measuring quality of care is essential. For Germany, data on care experiences in the last year of life that go beyond diagnoses and care settings are still rare. The aim of this study was to develop and validate a German version of the 'Views of Informal Carers' Evaluation of Services - Short Form (VOICES-SF)' suitable to assess the quality of care and services received across settings and healthcare providers in the German setting in the last year of life (VOICES-LYOL-Cologne). Methods VOICES-SF was adapted and translated following the 'TRAPD' team approach. Data collected in a retrospective cross-sectional survey with bereaved relatives in the region of Cologne, Germany were used to assess validity and reliability. Results Data from 351 bereaved relatives of adult decedents were analysed. The VOICES-LYOL-Cologne demonstrated construct validity in performing according to expected patterns, i.e. correlation of scores to care experiences and significant variability based on care settings. It further correlated with the PACIC-S9 Proxy, indicating good criterion validity. The newly added scale "subjective experiences of process and outcome of care in the last year of life" showed good internal consistency for each given care setting, except for the homecare setting. Test-retest analyses revealed no significant differences in satisfaction ratings according to the length of time since the patient's death. Overall, our data demonstrated the feasibility of collecting patient care experiences reported by proxy-respondents across multiple care settings. Conclusion VOICES-LYOL-Cologne is the first German instrument to analyse care experiences in the last year of life in a comprehensive manner and encourages further research in German-speaking countries. This instrument enables the comparison of quality of care between settings and may be used to inform local and national quality improvement activities. Trial registration This study was registered in the German Clinical Trials Register (DRKS00011925; Date of registration: 13/06/2017).